Paleoenvironments of the western Kawas Sea (Late Cretaceous-Paleocene) of Patagonia, Argentina - Aguirre Urreta, Beatriz (2011)
Fil: Aguirre Urreta, Beatriz. Instituto de Estudios Andinos (IDEAN, UBA- CONICET); Argentina.